Myth as a way of expressing the author’s modality (Eurasian Journal of Philology Science and Education, 2021)
The article substantiates the concept of modality in the linguistic research context. It offers a brief history of the modality category study in modern linguistic stylistics and linguistics of the text. Based on the method of theoretical material synthesis the study proposes the definition of “author’s modality” category. The “author’s modality” category, considered in the research, regards both linguistic and literary issues. The literary issues are connected with the study of the works by the Kazakh writer A. Kekilbayev and the Kyrgyz writer Sh.Aitmatov. The linguistic part of the study is associated with the text linguistics, fiction stylistics, structural and communicative syntax. The study of author’s modality and position in a literary text requires an integrated approach. The article examines the text-forming function of the “author’s modality” category in a literary text. As a result of considering the author’s modality transmission in the text using implicit means there determined the communicative pragmatic aspect of text formation. The author’s modality in the language of fiction is implemented through the elements of the lexical-grammatical and compositional levels of the text, and through the pragmatic-ideological units determined as a result of text perception, such as images, themes, author’s ideas and concepts. In the literary text, mythical plots, symbolism were considered as one of the ways to convey the author’s modality. There were presented examples from fiction works, contextual and component analysis was carried out. Since myth does not directly correlate with reality, the connection between myth and reality, including modern reality, acquires a conventional symbolic, coded character, which is reflected at the level of mythological reminiscences. The author uses this approach to express his attitude to a certain situation, concept and modality. The semantics of these structures includes various shades of modality, the definition of which allows to reveal the author’s intention. Key words: author’s modality, literary (fiction) text, national worldview, mythical plot, symbolic sign